Effects of reading and spelling predictors before and after school entry: Evidence from a German longitudinal study. (February 2019) - Schmitterer, Alexandra M.A.; Schroeder, Sascha
Abstract: Previous studies indicate that the effectiveness of reading and spelling predictors in transparent orthographies is affected by the onset of literacy training at school entry. In this longitudinal study with 65 German speaking children, the effects of literacy predictors on reading and spelling abilities were compared before and after school entry. Phonological awareness, letter sound knowledge, and rapid naming were assessed before and after school entry. In addition, reading and spelling abilities were assessed at the end of first grade. Path model analyses showed that letter sound knowledge before school entry predicted reading and spelling at the end of first grade, while rapid naming after school entry predicted reading but not spelling abilities. This study shows that the onset of schooling influences the predictability of early literacy predictors and indicates that with the onset of formal literacy education, predictors representing automaticity in serial processing increase in significance for reading abilities. Highlights: Trajectory of predictor effects across school entry in transparent orthography. Children in educational environment without literacy training before school entry. Differences in prediction of reading and spelling abilities before and after school entry. Influence of letter knowledge decreases. Influence of rapid naming increases.